2000
DOI: 10.1051/aas:2000217
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of line-profile variability in P Cygni's optical spectrum

Abstract: Abstract. High-resolution photographic spectra as well as high S/N ratio CCD spectral observations of P Cygni are analyzed in terms of line-profile variability (lpv). Four different kinds of lpv are established: systematic variability in the absorption troughs of low and intermediate excitation lines due to propagating Discrete Absorption Components (DACs); "swaying" variability consisting of continuous modulations in velocity and intensity of the absorption cores and emission peaks of lines of intermediate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
2
17
1
Order By: Relevance
“…Additionally we have found some new features of the objects. In particular, our spectra suggest that HD 168625 (B6 Ia + ) and HD 183143 (B7 Ia) could be considered as candidate objects showing "blueward migrating DACs" (e.g., Markova 2000). We also suggest a new explanation for the complicated shape of the absorption line profiles in the spectrum of AS 314.…”
Section: Discussionmentioning
confidence: 56%
“…Additionally we have found some new features of the objects. In particular, our spectra suggest that HD 168625 (B6 Ia + ) and HD 183143 (B7 Ia) could be considered as candidate objects showing "blueward migrating DACs" (e.g., Markova 2000). We also suggest a new explanation for the complicated shape of the absorption line profiles in the spectrum of AS 314.…”
Section: Discussionmentioning
confidence: 56%
“…This supports our study. Thus, we conclude that, during the last two decades, although in quiescence, P Cygni experienced at least two low-amplitude SD cycles with several short-term microvariations (de Groot et al 2001a,b;Markova 2000; superimposed.…”
Section: Discussionmentioning
confidence: 58%
“…The time scale of the SD oscillations is obviously too long to be explained in terms of pulsation instability like strange-mode oscillations (Kiriakidis et al 1993;Glatzel et al 1999), gravitymode oscillations or relaxation oscillations (Stothers & Chin 1995. On the other hand, the only mechanism that could produce phases of enhanced mass-loss rate in LBVs which repeat on time scale of years to decades are quasi-secular oscillations of the stellar envelope between dynamical stable and unstable states, according to the theoretical evolutionary tracks of Stothers & Chin (1995, 2000. Van Genderen (2001) suggested that the long SD-phases could perhaps be identified with the "secular cycles" in Stothers & Chin's models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that a variation in the continuum will act in a direction opposite to the measured emission and absorption equivalent width. Motivated by this possibility, Markova (2000a) has recently performed an extensive study of line-profile variability in P Cygni's optical spectrum including more than 60 lines formed in different layers of the stellar wind. The results obtained show that line-strength variations (both in absorption and emission), similar to and in phase with the ST variability traced by Hα, do in fact occur in almost all lines in the optical, including the strongest lines of SiIV, which presumably form near or at the base of the supersonic wind.…”
Section: Discussionmentioning
confidence: 99%